2015
DOI: 10.1088/0953-4075/48/12/125701
|View full text |Cite
|
Sign up to set email alerts
|

X-ray Thomson scattering diagnostics of impact ionization in laser-driven carbon foils

Abstract: Abstract.We have studied the light-matter interaction of ultra-short, intense optical laser fields with thin carbon foils via particle-in-cell simulations. Especially, the influence of additional impact ionization on the density and temperature of the generated plasma and on the corresponding Thomson scattering spectra was investigated which has been found essential for laser intensities I > 10 16 W/cm 2 . We predict a pump-probe experiment at the free electron laser FLASH in order to verify the importance of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Unless otherwise stated, the impact ionization is switched-off. Test runs showed that for the intensities considered here the effect of collisional ionization during the laser pulse is much smaller than that of field ionization [29,43].…”
Section: Plasma Generation In He Jetsmentioning
confidence: 88%
See 1 more Smart Citation
“…Unless otherwise stated, the impact ionization is switched-off. Test runs showed that for the intensities considered here the effect of collisional ionization during the laser pulse is much smaller than that of field ionization [29,43].…”
Section: Plasma Generation In He Jetsmentioning
confidence: 88%
“…The collisions of charged particles and neutral particles are considered utilizing a Monte-Carlo scheme [50], where different processes might occur; the interaction of electrons with neutral particles may lead to impact ionization, excitation, or elastic scattering. Test runs showed that for the intensities considered here the effect of collisional ionization during the laser pulse is much smaller than that of field ionization [29,51].…”
Section: Plasma Generation In He Slabsmentioning
confidence: 88%
“…The density and temperature profiles throughout the target are usually inhomogeneous. The resulting compression factor, degree of ionization, and temperature are dependent on the intensity and length of the laser pulse, its shape, and spot size . XRTS is then used to probe the WHDM state.…”
Section: Introductionmentioning
confidence: 99%
“…Via impact ionization, they heat the interior of the target [21,22]. This is an important effect for the fundamental understanding of the laser-driven generation of plasmas on ultra-short time scales [20,23], the excitation of clusters [24,25], and for applications like inertial confinement fusion.…”
Section: Introductionmentioning
confidence: 99%